Case based measles surveillance performance in 2010, littoral region of Cameroon - Gerald Etapelong Sume; Marie Kobela; Dieula Delissaint; Ditu Kazambu; Irène Emah (AOSIS, 2014)
The Littoral region of Cameroon met most of its routine immunization and surveillance objectives in 2010 but has not reiterated such a performance since then. We describe the casebased measles surveillance performance of 2010 by person, place, time and determine measles surveillance system delays. Descriptive statistics were performed using Epi Info 3.5.3. There were 130 suspected measles cases investigated by 17 (89.5%) health districts, 83 (64%) males and 99 (76%) ≤5 years. At least 4 cases were investigated per month with a peak of 23 cases in June. About 67 (51.5%) patients visited a hospital more than 48 h after disease onset, 34 (26.2%) health facilities informed the district service late after receiving a suspected case and 65 (50%) samples got to the reference laboratory more than 24 h after reception by the specimen collection centre. More than 2 discarded measles/100,000 population were investigated but with health facilities, specimen collection centre and patients' ability to seek healthcare delays. All specimens got to the reference laboratory within 72 h. Patients' health seeking behavior need to be improved and personnel involved in surveillance sensitized on timeliness.